Census data-the missing link: are we shooting in the dark? - Shah, Pappu Prasad; Goel, Manu (International Journal Of Community Medicine And Public Health, 2025)
The 16th Census of India was supposed to be held in 2021 however it was indefinitely delayed. This impacted the various administrative, policy and health planning efforts by the government of India. An extensive literature search was carried out using search engines like PubMed, Google scholar etc. Relevant articles in newspapers and policy documents pertaining to the Census were searched for. The authors reviewed the available literature and determined that the delay in conducting the Census impacted various sectors of India, from policymaking, health, business to administration. The authors concluded that the delay in conduction of the Census had severely impacted Indian polity and evidence-based decision making in heath programming. Thus, the government must conduct the Census at the earliest to ensure up to date data for adequate planning of programmes and policies to improve the lives of the citizenry.